IMPLEMENTASI KEBIJAKAN PENGAWASAN BARANG BEREDAR DAN PERLINDUNGAN KONSUMEN DI PROVINSI PAPUA BARAT - Sulafah Fathin Khannanah (Dialogue : Jurnal Ilmu Administrasi Publik, 2026)
Market surveillance of goods and services is a strategic function of local government aimed at ensuring consumer protection and fostering an orderly and healthy trade environment. In West Papua Province, the rapid growth of trade and service sectors throughout 2025 has generated both economic benefits and regulatory challenges, particularly regarding business compliance with legal standards, product safety, sanitation, and price fairness. This study aims to analyze the implementation of market surveillance policies on goods and services based on empirical findings from inspection activities conducted by the Provincial Office of Industry and Trade in 2025. The scope of the study covers various commodities and service sectors, including basic necessities and services directly related to public health. This research employs an empirical approach with descriptive qualitative analysis using field inspection data as the primary source. The results indicate that policy implementation has not yet been optimal, as evidenced by persistent non-compliance among business actors and structural constraints faced by local authorities, such as limited resources and supervisory capacity. Furthermore, the findings reveal that policy implementation tends to follow an incremental approach rather than a rational and systematic model as outlined in public policy theory. In conclusion, strengthening institutional capacity, improving regulatory compliance, and enhancing coordination among stakeholders are essential to improving the effectiveness of market surveillance and consumer protection policies in West Papua Province.